2015
DOI: 10.1016/j.exer.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Implications for ocular disease and therapeutic potential

Abstract: Vitamin D is a multifunctional hormone that is now known to play a significant role in a variety of biological functions in addition to its traditional role in regulating calcium homeostasis. There are a large number of studies demonstrating that adequate vitamin D levels are important in maintaining health and show that vitamin D is able to be utilized at local tissue sites. In the eye, we have increasing evidence of the association between disease and vitamin D. In this narrative review, we summarize recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 118 publications
(136 reference statements)
0
65
0
3
Order By: Relevance
“…Calcitriol signalling through the nuclear VDR regulates over 900 genes in a micro‐environment‐specific manner (Alexander et al, ; Kongsbak et al, ). In the human eye, the VDR is expressed in the, photoreceptors, RPE, lens, cornea, ganglion cell layer and ciliary body (Johnson et al, ; Reins and McDermott, ). Expression of zebrafish VDR paralogues, vdra and vdrb arising from gene duplication, was validated here in larval eyes at 5 dpf by RT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol signalling through the nuclear VDR regulates over 900 genes in a micro‐environment‐specific manner (Alexander et al, ; Kongsbak et al, ). In the human eye, the VDR is expressed in the, photoreceptors, RPE, lens, cornea, ganglion cell layer and ciliary body (Johnson et al, ; Reins and McDermott, ). Expression of zebrafish VDR paralogues, vdra and vdrb arising from gene duplication, was validated here in larval eyes at 5 dpf by RT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…[2938] Regarding myopia, several previous studies have found that low hydroxyvitamin D is associated with a high prevalence of myopia in young populations. [36,37,39] However, there is controversy as to whether 25(OH)D is an independent factor for progression of myopia. [3840] To date, the possible independent associations of serum vitamin D levels and sunlight exposure time with myopia have not been sufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…10 Due to its pleiotropic nature, the level of active forms of vitamin D has been associated with various diseases including those related to the eye. 10,11 Furthermore, there is growing evidence regarding the association of vitamin D with chronic pain. 9,12 An increase in the levels of inflammatory cytokines has been reported in DED 13,14 and some with the ability to modulate pain sensation.…”
Section: Introductionmentioning
confidence: 99%